Arabidopsis stress associated protein 9 mediates biotic and abiotic stress responsive ABA signaling via the proteasome pathway. (24th February 2017) - Kang, Miyoung; Lee, Seonghee; Abdelmageed, Haggag; Reichert, Angelika; Lee, Hee‐Kyung; Fokar, Mohamed; Mysore, Kirankumar S.; Allen, Randy D.
Abstract: Arabidopsis thaliana Stress Associated Protein 9 (AtSAP9) is a member of the A20/AN1 zinc finger protein family known to play important roles in plant stress responses and in the mammalian immune response. Although SAPs of several plant species were shown to be involved in abiotic stress responses, the underlying molecular mechanisms are largely unknown, and little is known about the involvement of SAPs in plant disease responses. Expression of SAP9 in Arabidopsis is up‐regulated in response to dehydration, cold, salinity and abscisic acid (ABA), as well as pathogen infection. Constitutive expression of AtSAP9 in Arabidopsis leads to increased sensitivity to ABA and osmotic stress during germination and post‐germinative development. Plants that overexpress At SAP9 also showed increased susceptibility to infection by non‐host pathogen Pseudomonas syringae pv. phaseolicola, indicating a potential role of AtSAP9 in disease resistance. AtSAP9 was found to interact with RADIATION SENSITIVE23d (Rad23d), a shuttle factor for the transport of ubiquitinated substrates to the proteasome, and it is co‐localized with Rad23d in the nucleus. Thus, AtSAP9 may promote the protein degradation process by mediating the interaction of ubiquitinated targets with Rad23d. Taken together, these results indicate that AtSAP9 regulates abiotic and biotic stress responses, possibly via the ubiquitination/proteasome pathway. Abstract : While the role of certain members of a family of stress associated proteins (SAPs) that contain A20 and An1 zinc finger domains in abiotic stress responses in plants is well established, emerging data shows possible roles for SAPs in other cellular responses. Our research confirms that SAP9 from Arabidopsis (AtSAP9) has ubiquitin ligase activity and is a positive regulator of ABA signaling. Our results also provide evidence for the involvement of AtSAP9 in plant development and disease responses. In addition, we show that AtSAP9 physically binds to the ubiquitin receptors Rad23A and Rad23D, indicating that, in addition to acting as a ubiquitin ligase, SAP9 may function in the UPS system by directing ubiquitinated substrates to the proteasome through interaction with ubiquitin receptors.